Early-middle Eocene chronology of the Southern Ocean: magnetostratigraphic data from the South Island of New Zealand - E. Dallanave; V. Bachtadse; C. Agnini; C. J. Hollis; H. E. Morgans; J. S. Crampton; G. Muttoni (2012)
During the Paleogene the Earth experienced a pronounced warming trend culminating with the early Eocene climatic optimum (EECO, ~52-50 Ma), which was followed by a long-term cooling trend over the middle-late Eocene. This long-term climate evolution was punctuated by several transient (~10^3-5 yr) hyperthermal events (e.g. Paleocene Eocene thermal maximum). Even though great advances have been made in the last few years in understanding the paleoclimate history of the southwestern Pacific Ocean and the implications on the sedimentation patterns, a precise correlation between sites and global events is still missing. This is mainly because of the poor preservation of calcareous nannofossils, diachronous ranges of index species, and a lack of a good magnetic polarity reversals record. We present preliminary early-middle Eocene magnetostratigraphy from the Mid Waipara and the Mead Stream marine sections, cropping out in the South Island of New Zealand. These sections provide the best-known record of oceanic changes in the southern Pacific high-latitude (50-60°S) for this time period. Magnetostratigraphic data, integrated with new and published biostratigraphy, indicates that the sampled ~45 m of the Mid Waipara section straddles polarity Chrons from C23n to C21n (~51.5-47 Ma), with an average sediment accumulation rate of ~9 m/Myr, calculated by means of correlation with the GPTS2004 time scale. This robust chronological framework allow to constrain in time the paleotemperature dataset of Hollis et al. (EPSL 349-350, pp. 53-56, 2012), confirming that the Ashley Mudstone formation of Mid Waipara includes at least the upper part of the EECO and the early-middle Eocene transition. The sampled ~320 m of the Mead Stream section, which comprises the three upper member of the Amuri Limestone (Lower Marl, Upper Limestone and Upper Marl), encompass polarity Chrons from C24r to C18r (~55-40 Ma), with an average sedimentation rate of ~17 m/Myr. We confirm evidence from carbon isotopes (Slotnick et al., J. Geol. 120, 2012) and ...